Inspection system for woven fabrics of some selected garment exporters in Pasig City - Agulto, Clarissa Barreto
Fabric inspection is a very important component of the quality control system of a garment manufacturing company. It is a process undertaken to detect defect that could make the fabric substandard or second quality. This study was conducted to provide the garment industry information on the fabric inspection systems of some selected garment exporters in Pasig City. In addition, to make them more aware of the importance of fabric inspection for the early detection of fabric defects. The fabric inspection systems of five garment companies located in Pasig City were identified in this study through interviews with the fabric inspectors and observations of the fabric inspection, qualification of the fabric inspectors, equipment used, frequency of fabric inspection, percentage of the fabric lot that was inspected, point system used for grading defects, common fabric defects, method of dealing with fabric defect, and methods of dealing with rejected fabrics. The data gathered for each company were compared with the Philippine Textile Research Institute Standard procedure for Grading Finished Woven Fabrics or PTRI 71:1979(88). Results showed that all the companies had their own fabric inspection systems and were comparable to the PTRI Standard in terms of equipment used, the point system of grading, the point computation and the method of dealing with reject fabrics. The standard fabric inspection system of each company was based on the quality requirements of the market, the quality control system, the size of the company, and the requirements of the buyer.